Evaluating the Role of Intrathecal Chemotherapy in CNS Prophylaxis for Pediatric Leukemias: A Retrospective Study - Karim, Sumera Abdul; Abbas, Sumbal; Gillani, Syeda Tehreem Zahra; Gillani, Syeda Urooj Fatima; Jameel, Madiha; Shaheen, Najma (Biological and Clinical Sciences Research Journal, 2025)
The central nervous system (CNS) is a sanctuary site for leukemic cells in pediatric acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML), necessitating targeted prophylaxis. Objective: To evaluate the effect of IT chemotherapy intensity on CNS relapse-free survival (CNS-RFS) in pediatric leukemia patients. Methods: This retrospective observational study was conducted at Shaukat Khanum Memorial Cancer Hospital and Research Center from 2023 to 2024. A total of 150 pediatric patients (118 ALL, 32 AML) were included in the study. Patients were categorized as receiving full-intensity (≥90% of planned IT doses) or reduced-intensity (<90%) CNS prophylaxis. Results: Of the cohort, 108 patients (72.0%) received full-intensity IT chemotherapy and 42 (28.0%) received reduced-intensity. Over a median follow-up of 48 months, CNS relapse occurred in 4 patients (3.7%) in the full-intensity group versus 10 patients (23.8%) in the reduced-intensity group (p < 0.001). Five-year CNS-RFS was significantly higher with full-intensity prophylaxis (96.0% vs. 71.4%, p < 0.001). Multivariable analysis showed reduced-intensity IT was independently associated with increased CNS relapse risk (HR 4.85; 95% CI: 1.78–13.21; p = 0.002). Neurotoxicity occurred in 7.3% of patients, mostly reversible, and procedural complications occurred in 5.3%, with no permanent deficits. Conclusion: Full-intensity IT chemotherapy is strongly associated with lower CNS relapse rates and improved CNS-RFS in pediatric leukemia, particularly in high-risk subgroups. Minimizing treatment interruptions and addressing logistical barriers are essential to maintain optimal CNS prophylaxis, especially in the era of reduced cranial irradiation.